Penggunaan Visual Studio untuk Pembuatan Aplikasi Jual Beli Elektronik Berintegrasi MySQL - Putra, Julio Anggara; Ardhani, Nandhana; Basatha, Rizky (Al-DYAS, 2025)
In the ever-growing digital era, buying and selling electronic goods has become important for the lives of ordinary people. This research aims to develop a sales application aimed at the buying and selling aspect of electronic goods which makes it easier for sellers to manage goods and sales and makes it easier for buyers to find and buy the desired electronic goods. This application was developed by considering important features such as user login, item list, item search, shopping cart, print purchase form. With the aim of increasing security and shopping comfort, this application is aimed at increasing sales and customer comfort in making purchasing transactions. It cannot be separated from competitors' challenges, data privacy security, and application performance improvements so that users are more comfortable in operating the application.